Successful surgical management of multiple foreign bodies in a captive green iguana (Iguana iguana) - Naktap, Sirapoom; Seawyim, Naweeya; Dusitkul, Kanyanut; Duangurai, Taksaon (Journal of Mahanakorn Veterinary Medicine, 2025)
A 3.5-year-old male green iguana (Iguana iguana) presented with a two-week history of anorexia, absence of defecation, and dysecdysis. Physical examination revealed abdominal distension and discomfort. Initial radiographs identified multiple coins and sharp radiopaque objects within the large intestine, along with intestinal gas accumulation. Due to the size, position, and number of the foreign bodies, surgical intervention was deemed necessary. The patient was pre-medicated intramuscularly with a combination of ketamine, midazolam, and dexmedetomidine, and anesthesia was maintained with isoflurane. An exploratory coeliotomy was performed through a paramedian incision. The cecum was isolated, and typhlotomy was performed to remove the foreign bodies, which included six coins and several small stones. Incisions were closed, and the patient recovered uneventfully from the operation. Postoperative care included supportive fluid therapy, analgesia, and assisted feeding until a normal appetite resumed. Follow-up radiographs showed a clear gastrointestinal tract with improved intestinal motility. By postoperative day ten, the patient had shown complete resolution of clinical signs and a return to a normal appetite and defecation. This case report highlights the importance of prompt diagnosis and timely surgical intervention when multiple foreign bodies are present. It also underscores the need for proactive client education to prevent recurrence.